Geographical Diversity and its Influence on Rice Yield - Parimal Kanti Biswas; Dimitrios Ntanos (Agriculture and Natural Resources, 2002)
Experiments were conducted at two different geographical locations, the Asian Institute of Technology, Thailand and the Cereal Institute, Thessaloniki, Greece to compare tillering and yield of locally recommended rice varieties. Rice varieties RD23 and KDML105 of Thailand gave the same number of tillers at harvest and delayed planting (September 14) showed higher number of tillers/hill compared to early planting though there were no significant variations of panicles/m2 observed among different planting dates. The variety RD23 resulted in significantly higher grain yield (3.7 t/ha) compared to KDML105 (2.9 t/ha). The variety KDML105 showed higher 1000-grain weight (26.3 g) with longer duration (125 days) and lower HI (0.27) compared with RD23. Planting up to August 14 resulted in higher grain yield and 1000-grain weight, but delayed planting showed lower yield as well as grain weight. The indica type rice variety Olympiada showed significantly higher number of tillers/hill (19.8) at harvest compared with other japonica-typed varieties. The variety Maratelli resulted in lowest grain yield (5.7 t/ha). Indica typed variety showed higher panicles/m2 (319) with higher HI (0.57) but less 1000-grain weight (24.0 g) compared with other japonica typed varieties. Tropical rice showed lower grain yield, HI and maturity duration compared with temperate rice.